Rebuilding Participatory Institutions in Brazil: The PPA Participativo Between Corporate Demands and Climate and Animal Rights - Priscila Delgado de Carvalho; Priscila Zanandrez; Diego Matheus de Menezes (Societies)
In 2023, Brazil regained momentum in proposing innovative participatory institutions by launching a complex participatory experiment for budget planning within its “Multiannual Plan” (PPA). While this was not a scaled-up version of the local participatory budgeting plan that emerged decades earlier, its launch did reopen the debate on the possibilities of expanding political participation. The challenge was significant due to the intricate nature of budget planning and the complexity of the plan’s participatory design. This paper examines that experience by outlining the institutional design of the PPA Participativo and analyzing its results in terms of online participation. It also discusses the prominence of climate-related proposals, suggesting that the PPA Participativo serves as a relevant indicator of national concerns regarding climate-based issues. Building on previous experiences, the PPA Participativo is a strategy consisting of three layers: an online platform for digital participation, state-level meetings with civil society activists, and a high-level forum composed of members from national councils. This paper analyses some of the results from the online platform, which recorded 4 million visits from 1.5 million individual participants. These citizens were invited to submit proposals, vote for up to three proposals, and choose from a set of pre-designed government programs. The main concerns that emerged from this open-ended process included corporate demands, stemming from highly organized sectors, such as public health and education employees. However, animal rights also ranked among the most-voted proposals. The program of the Ministry of the Environment on climate change reached the top position in this segment, largely due to its strong campaigning strategy. This paper discusses these outcomes, drawing on evidence of both societal engagement and institutional activism to promote specific agendas.